Long-term consequences of developmental vascular defects on retinal vessel homeostasis and function in a mouse model of Norrie disease - Becker, Susanne Christiane; Feng, Yuxi; Shan, Shenliang; Hammes, Hans-Peter (PLOS ONE, 2017)
Loss of Norrin signalling due to mutations in the Norrie disease pseudoglioma gene causes severe vascular defects in the retina, leading to visual impairment and ultimately blindness. While the emphasis of experimental work so far was on the developmental period, we focus here on disease mechanisms that induce progression into severe adult disease. The goal of this study was the comprehensive analysis of the long-term effects of the absence of Norrin on vascular homeostasis and retinal function. In a mouse model of Norrie disease retinal vascular morphology and integrity were studied by means of in vivo angiography; the vascular constituents were assessed in detailed histological analyses using quantitative retinal morphometry. Finally, electroretinographic analyses were performed to assess the retinal function in adult Norrin deficient animals. We could show that the primary developmental defects not only persisted but developed into further vascular abnormalities and microangiopathies. In particular, the overall vessel homeostasis, the vascular integrity, and also the cellular constituents of the vascular wall were affected in the adult Norrin deficient retina. Moreover, functional analyses indicated to persistent hypoxia in the neural retina which was suggested as one of the major driving forces of disease progression. In summary, our data provide evidence that the key to adult Norrie disease are ongoing vascular modifications, driven by the persistent hypoxic conditions, which are ineffective to compensate for the primary Norrin-dependent defects.